Occupational Injuries and Use of Benzodiazepines: A Systematic Review and Metanalysis - Garbarino, Sergio; Lanteri, Paola; Bragazzi, Nicola Luigi; Gualerzi, Giovanni; Riccò, Matteo (Frontiers in Human Neuroscience, 2021)
Background. Benzodiazepines have been widely used in clinical practice for over four decades and continue to be one of the most consumed and highly prescribed class of drugs available in the treatment of anxiety, depression, and insomnia. The literature indicates that Benzodiazepine users at a significantly increased risk of Motor Vehicle accidents compared to nonusers but the impact on injuries at workplace is not well defined. We aimed to investigate whether use of benzodiazepine is associated with increased risk of occupational injuries (OI). Methods. PubMed, Embase and Scopus databases were searched. A meta-analysis was performed to calculate odds ratio (OR) and 95% confidence interval (CI) among case controls, cross-sectional studies, either questionnaire or laboratory exams based. Results. A total of 13 studies met inclusion criteria, involving 324,168 OI from 7 different countries, with an estimated occurrence of benzodiazepine positivity of 2.71% (95%CI 1.45-4.98). A total of 14 estimates were retrieved. Of them, 10 were based on laboratory analyses, 3 on institutional databases, while 1 study was based on questionnaires. Regarding the occupational groups, 3 estimates focused on commercial drivers (0.73%, 95%CI 0.12-4.30), that exhibited a reduced risk ratio for benzodiazepine positivity compared to other occupational groups (RR 0.109, 95%CI 0.063-0.187). Eventually, no increased risk for benzodiazepine positivity was identified, either from case control studies (OR 1.520, 95%CI 0.801-2.885, I2 76%), or cross sectional studies, when only laboratory based estimates were taken in account (OR 0.590, 95%CI 0.253-1.377, I2 63%). Conclusions. Even though benzodiazepines have the potential to increase injury rates among casual and chronic users, available evidence are insufficient to sustain this hypothesis, particularly when focusing on laboratory-based studies (i.e. studies the characterized the benzodiazepine immediately before the event).